The Influence of Safety Climate on Safety Performance among Assistant Medical Officer at Government Health Facilities in Kuantan Pahang Darul Makmur - Basri, Faizal Reza (2020)
The purpose of this thesis is to study the relationship and influence of the safety climate and the safety performance of assistant medical officers in health facilities throughout Kuantan Pahang. The chosen safety climate consists of several dimensions, namely, management commitment, employee involvement, and worker satisfaction. To obtain the validity of the study objectives, 94 sets of questionnaires were distributed to the assistant medical assistant at all health facilities in the Kuantan Pahang district and only 84 forms were successfully collected. However, they still met the targets suggested by the researchers-Krejcie and Morgan in 1970. Collected data were processed using SPSS software system version 23. Pearson's correlation analysis test found that there was a strong and positive relationship between the safety climate (worker involvement and job satisfaction) with safety performance. There is only one dimension of the safety climate, which is the management commitment, who has no significant relationship with safety performance. Nevertheless, for multiple regression analysis tests, there is an influence on safety performance by all dimensions of safety climate. For conclusion, although all variables safety climate except management commitment, have positive and significant corelated toward safety performance, however the impact will more larger if management commitment is playing more important part in safety and health related issues in an organization. At the end of the study, the implications of the study is need were uncovered and finally, opinions and recommendations for improving safety performance were outlined for future studies.